The Performance of PT TA Assets Indonesia Employees is Influenced By The Provision of Salaries Through Job Satisfaction - Eddy Sanusi Silitonga (Dinasti Publisher, 2023)
The purpose of this study was to analyze and determine the positive and significant effect of salary on employee performance through job satisfaction as an intervening variable at PT. TA Asset Indonesia. The subjects in this study were all employees of PT. TA Asset Indonesia using a quantitative approach method. Meanwhile, to analyze the pattern of relationships between variables in this study using path analysis with the aim of knowing the direct or indirect effect of a set of independent variables on the dependent variable. The results of this study state that there is a direct influence between salary on employee performance at PT. TA Asset Indonesia with going through job satisfaction.